الوجيز في قانون المجتمع الدولي (التطور والأشخاص) - حوبة, عبد القادر (University of Eloued جامعة الوادي, 2020)
This book deals with a brief study of the contemporary international community, which is the main basis for studying the principles of general international law, as the first chapter includes a historical overview related to the development of the international community through the ages to our present time, starting from the international community in the ancient times and then the international community in the Middle Ages. It also includes a glimpse of the modern European international community (1492-1914), as well as the contemporary international community. Part of the study is devoted to studying the principles of the international community from an Islamic perspective, because the concept of the international community in Islam is not linked to a certain period of time. It is a permanent concept linked to the concept of the state in Islam and its relations with other nations in any age. The book includes in the second part a study of the people of the international community, which is mainly represented in the state and international organizations. It also includes a study of the individual's position in international law as it represents a major development in this area. Finally, the book contains a brief study related to national liberation movements and multinational companies, considering their impact on the reality of international relations.
An introduction to contemporary international community law
كتاب. إصدارات مخبر الدراسات الفقهية والقضائية. جامعة الوادي
Keywords: قانون المجتمع الدولي، التطور، الأشخاص